Effects of Subtypes of Child Maltreatment on CRP in Adulthood - Bitsika, Vicki; Sharpley, Christopher F.; McMillan, Mary E.; Jesulola, Emmanuel; Agnew, Linda L. (Frontiers in Psychiatry, 2021)
In order to evaluate the effects of specific forms of childhood maltreatment (CM) upon adult C-reactive protein (CRP) concentrations, and to further describe the potentially confounding role that recent life stress and depression hold in that relationship, 221 participants from rural Australia (M age = 44yr, SD = 17.8yr) completed self-report questionnaires and provided a blood sample. There were no sex differences in any variables across the 91 males and 130 females, but depression status did confound the association between global CM and CRP. The specific active ingredient of CM was identified as physical and mental health abuse, and this was significantly associated with CRP level in both depressed and non-depressed participants. There was no significant confound from recent life stressors. Results hold implications for the diagnosis of CM-related CRP elevation and (potentially) depression.